Forecasts of non-religious processes in Ukraine - Fylypovyč, Ljudmyla Oleksandrivna (Ukrai͏̈ns'ke relihijeznavstvo, 2008)
Recognizing that our prediction attempt is far from truly scientific prognosis, which requires knowledge of prediction theory and the experience of using the latter in a particular type of socio-spiritual reality - religion, it still makes sense to reflect on the future of new religious movements (NRR) in Ukraine, satisfying and pure research interest, and the need for modern publiclife.